2018
DOI: 10.3390/rs10081317
|View full text |Cite
|
Sign up to set email alerts
|

Using Multi-Angle Imaging SpectroRadiometer Aerosol Mixture Properties for Air Quality Assessment in Mongolia

Abstract: Ulaanbaatar (UB), the capital city of Mongolia, has extremely poor wintertime air quality with fine particulate matter concentrations frequently exceeding 500 μg/m3, over 20 times the daily maximum guideline set by the World Health Organization. Intensive use of sulfur-rich coal for heating and cooking coupled with an atmospheric inversion amplified by the mid-continental Siberian anticyclone drive these high levels of air pollution. Ground-based air quality monitoring in Mongolia is sparse, making use of sate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 26 publications
(42 reference statements)
2
14
0
Order By: Relevance
“…In terms of exposure estimation, MISR AOD products resulted in better and more robust estimates than did AOD mixtures, except for dust. Non-linear models (GBM, RF, and SVM) performed better than linear models (Ridge and LASSO), which was consistent with previous studies where linear models were inadequate in explaining the relationship between AOD and ground-monitored PM [22,35,46]. Although MISR aerosol data have coarser temporal and spatial resolution compared to MAIAC (every 3-5 days vs. daily and 4.4 km vs. 1 km, respectively), our model achieved high prediction performance (Table 1) using MISR-specific data products on size, shape, and absorption, which proved vital in the prediction models.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In terms of exposure estimation, MISR AOD products resulted in better and more robust estimates than did AOD mixtures, except for dust. Non-linear models (GBM, RF, and SVM) performed better than linear models (Ridge and LASSO), which was consistent with previous studies where linear models were inadequate in explaining the relationship between AOD and ground-monitored PM [22,35,46]. Although MISR aerosol data have coarser temporal and spatial resolution compared to MAIAC (every 3-5 days vs. daily and 4.4 km vs. 1 km, respectively), our model achieved high prediction performance (Table 1) using MISR-specific data products on size, shape, and absorption, which proved vital in the prediction models.…”
Section: Discussionsupporting
confidence: 90%
“…We expand upon our previous work [22,35] to include MISR aerosol properties of absorption (absorbing or non-absorbing), shape (spherical or nonspherical), and type provided by 74 weighted aerosol optical depths (mixtures) [21] to predict PM 2.5 and PM 2.5 SO 2− 4 , NO − 3 , EC, and dust. We matched daily PM 2.5 and PM 2.5 speciation measurements from ground monitors to the nearest available MISR pixel within 4.4 km ( Figure A2) and then further matched them to the nearest gridMET pixel within 4 km.…”
Section: Exposure Estimation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the accuracy of fine-scale AOD features cannot be independently evaluated in this case, the aerosol spatial variability is consistent with field observations , and the V23 product provides the type of high-resolution, large-scale content that is needed for air quality applications. Garay et al (2017) demonstrated that a prototype version of the V23 4.4 km retrievals agree substantially better with ground-based observations than the previous V22 17.6 km retrievals, in that study MISR retrievals were compared against observations carried out during several AERONET-DRAGON deployments around the globe. This would be expected, especially in places where aerosol amount varies on kilometer spatial scales.…”
Section: Scene Comparisonsmentioning
confidence: 85%
“…To determine the origin of prevailing air masses, Sateesh et al used backward trajectories computed with the HYSPLIT model in India [13]. Additionally, Franklin et al used the Multi-Angle Imaging SpectroRadiometer (MISR) instrument onboard the NASA Terra satellite to reliably estimate ground-level concentrations of PM 2.5 and SO 2 in Ulaanbaatar, Mongolia [14]. Furthermore, Zheng et al obtained measurement data from Aura, a sun-synchronous orbit satellite, to describe the long-term spatiotemporal distribution of NO 2 , SO 2 , and trace gases, such as HCHO, BrO, and OCIO, in Inner Mongolia [4].…”
Section: Introductionmentioning
confidence: 99%